2020
DOI: 10.3390/v12020204
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Transcription Inhibitor 1E7-03 Restores LPS-Induced Alteration of Lung Leukocytes’ Infiltration Dynamics and Resolves Inflammation in HIV Transgenic Mice

Abstract: Human immunodeficiency virus (HIV)-infected individuals treated with anti-retroviral therapy often develop chronic non-infectious lung disease. To determine the mechanism of HIV-1-associated lung disease we evaluated the dynamics of lung leukocytes in HIV-1 transgenic (Tg) mice with integrated HIV-1 provirus. In HIV-Tg mice, lipopolysacharide (LPS) induced significantly higher levels of neutrophil infiltration in the lungs compared to wild-type (WT) mice. In WT mice, the initial neutrophil infiltration was fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In contrast, lung neutrophil (polymorphonuclear cells PMNC) levels were significantly elevated in HIV-Tg mice. Additionally, we observed the delayed resolution of both Mφ and PMNC lung infiltration in HIV-Tg mice that resulted in increased mortality [9]. Moreover, we demonstrated that HIV-1 expression in Mφ was associated with altered trans-endothelial Mφ migration in vitro and in mouse model.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…In contrast, lung neutrophil (polymorphonuclear cells PMNC) levels were significantly elevated in HIV-Tg mice. Additionally, we observed the delayed resolution of both Mφ and PMNC lung infiltration in HIV-Tg mice that resulted in increased mortality [9]. Moreover, we demonstrated that HIV-1 expression in Mφ was associated with altered trans-endothelial Mφ migration in vitro and in mouse model.…”
Section: Introductionmentioning
confidence: 70%
“…The accumulation of macrophages in lung capillaries may be explained by impaired Mφ trans-endothelial migration. Previously we demonstrated that trans-endothelial migration of HIV-Tg macrophages was reduced compared to WT macrophages in vitro, and inhibition of HIV-1 gene expression restored the ability of Mφs to migrate through endothelial cells [9].…”
Section: Expression Of Hiv-1 Genes Is Elevated In Lung Macrophages Comentioning
confidence: 85%
See 3 more Smart Citations